The Influence of Service Quality, Product Quality and Location on Purchasing Decisions (Study of Virgin Cake and Bakery Shop Custumors) - Fatmasari, Dewina; Jumai , Jumai (Economics and Business International Conference Proceeding, 2024)
The population in this research is all consumers of the Virgin Bakery Shop. The sample used in this research used the Slovin formula to obtain a sample of 100 people. The results of the research analysis obtained showthat: (1) Service Quality has nopositive and insignificant effect on purchasing decisions at Shopee. This isproven by the t count of 1.252 < t table 1.660, and a significance value of 0.000 < 0.05. (2) Product quality has a positive andsignificant effect on purchasing decisions.This is proven by the t count of 5.203 > t table 1.660 and asignificance value of 0.000 < 0.05. (3) Location has a positive and significant effect on purchasing decisions. This is proven by the t count of 3.678. t tableis 1.660, and the significance value is 0.000<0.05. (4) ServiceQuality, Product Quality and Location simultaneously have a positive and significant influence on purchasingdecisions. This is proven by the Fcount of 71.103, and a significance value of <0.05. Based on the percentage results through the coefficient of determination test in this study, it was 69%, which indicates that all independent variables influence purchasing.